The telecommunications handbook - Terplan, Kornel; Morreale, Patricia (CRC Press, 2000)
Contains telecommunications topics that include, Basic principles, Services on broadband networks, Signal processing and coding schemes, Mobile and wireless networks, DSL technologies, Digital video and multimedia, Quality of service, Regulation, Standards, and Emerging technologies.